2009
DOI: 10.1158/1541-7786.mcr-08-0493
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 Up-Regulates Ataxia Telangiectasia and Rad3 Related through Extracellular Signal-Regulated Kinase Activation

Abstract: Cyclooxygenase-2 (COX-2) overexpression caused prolonged G 2 arrest after exposure to ionizing radiation (IR) in our previous study. We were therefore interested in investigating the function of COX-2 in the G 2 checkpoint pathway. Interestingly, we found that cells in which COX-2 is overexpressed showed up-regulated ataxia telangiectasia and Rad3 related (ATR) expression compared with control cells. In this study, we investigated the mechanism of ATR up-regulation by COX-2 and tested our hypothesis that COX-2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Recently, we reported that COX-2 overexpressing cancer cells upregulate ataxia telangiectasia and rad3-related (ATR) expression and activity, and that upregulated ATR induces resistance to DNA damaging agents such as IR or hydroxyurea [39]. Therefore, upregulated ATR activity in COX-2 overexpressing cancer cells may compensate for the ATM activity inhibited by gefitinib, and thereby prevent MC.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we reported that COX-2 overexpressing cancer cells upregulate ataxia telangiectasia and rad3-related (ATR) expression and activity, and that upregulated ATR induces resistance to DNA damaging agents such as IR or hydroxyurea [39]. Therefore, upregulated ATR activity in COX-2 overexpressing cancer cells may compensate for the ATM activity inhibited by gefitinib, and thereby prevent MC.…”
Section: Discussionmentioning
confidence: 99%
“…COX-2 is also known to be involved in carcinogenic processes through various pathways ). Therefore, COX-2 is also regarded as an important target molecule for cancer treatment as we previously reviewed ( Jun et al, 2009;Kim et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Research to identify these common target molecules will not be easy. However, we focused on molecules involved in the G 2 checkpoint, especially ATR and ATM, because we previously found that COX-2 profoundly prolongs IR-induced G 2 arrest and it is caused by upregulation of ATR by COX-2 (Shin et al, 2005; Kim et al, 2009). In addition, hsp90 also has many client proteins involved in cell cycle regulation, including Chk1, which is directly downstream of ATR.…”
mentioning
confidence: 99%
“…In fact, COX-2 expression has been associated with several antiapoptotic pathways, such as induction of bcl-2 and subsequent survival mechanisms, or by induction of ATM and ATR in some solid tumors. 20 Furthermore, COX-2 has been associated with chemoresistance and radiation resistance by inducing neoangiogenesis and also because of its strong correlation with the expression of the MDR gene. 21 Nevertheless, the specific role of the COX-2 pathway in the pathogenesis of hematologic malignancies is not known.…”
Section: Discussionmentioning
confidence: 99%